Laboratory Profiles of Pleural effusion Collected from Children: Experience at a Tertiary Care Hospital in Bangladesh - Hasan, Mahmudul; Islam, Md Rafiqul; Matin, Abdul; Roy, Ranjit Ranjan; Yusuf, Md Abdullah; Karim, AKM Rezaul; Mowla, Md Golam; Islam, Md Reazul (Journal of Shaheed Suhrawardy Medical College, 2013)
Background: Pleural effusion occurs in many reasons. Laboratory tests are necessary to find out the causes. Objective: This study was an attempt to know the laboratory findings of pleural effusion. Methodology: This cross-sectional study of thirty (30) admitted cases with pleural effusion confirmed by chest radiography and aspiration of pleural fluid from one (1) year to twelve (12) years age of either sex were collected purposively. This study was carried out from July 2009 to February 2010 in the Department of Pediatrics at Rajshahi Medical College Hospital. All information were recorded in pre tested semi structured questionnaire. Results: Color of pleural fluid was straw in 56.7%, clear in 30.0%, blood stained in 13.3%. In this study, lymphocyte predominance among 56.7% cases, acid fast bacilli in 3.3% cases and raised protein of more than 3gm/dl and sugar less then 60mg/dl in 93.3% cases in pleural fluid. Conclusion: In almost all cases protein is raised and sugar is less in pleural fluid. DOI: http://dx.doi.org/10.3329/jssmc.v5i1.16201 J Shaheed Suhrawardy Med Coll, 2013;5(1):26-27